2014
DOI: 10.1186/1916-0216-43-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between survival and socio-economic status for head and neck cancer in Canada

Abstract: BackgroundHuman papilloma virus (HPV) is emerging as the primary cause for some head and neck cancers. The objective of this study was to investigate the association between head and neck cancer (HNC) survival and socioeconomic status (SES) in Canada, and to investigate changes in the relationship between HNC survival and SES from 1992 to 2005.MethodsCases were drawn from the Canadian Cancer Registry (1992–2005), and were categorized into three subsites: oropharynx, oral cavity, and “other” (hypopharynx, laryn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 14 publications
7
67
2
3
Order By: Relevance
“…The higher rate of cancer-related death in older patients is consistent with findings from other population-based studies of head and neck cancer (61,62), as is the positive association between area-level deprivation and mortality (63)(64)(65). Moreover, the fact that our smoking results were adjusted for deprivation makes socioeconomic confounding an unlikely explanation for our findings in relation to smoking.…”
Section: Other Sociodemographic Prognostic Factorssupporting
confidence: 91%
“…The higher rate of cancer-related death in older patients is consistent with findings from other population-based studies of head and neck cancer (61,62), as is the positive association between area-level deprivation and mortality (63)(64)(65). Moreover, the fact that our smoking results were adjusted for deprivation makes socioeconomic confounding an unlikely explanation for our findings in relation to smoking.…”
Section: Other Sociodemographic Prognostic Factorssupporting
confidence: 91%
“…All the aforementioned are among the important reasons for the low 5-year survival of patients as well as the higher mortality rates in developing countries (Funk et al, 2002;Global Burden of Disease Cancer, 2015;Patel et al, 2012;Sargeran et al, 2008). McDonald et al reported in their study that there was lower survival of head and neck cancers, including oral cavity cancer, in people of low socioeconomic statuses (McDonald et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…9 If cancer incidence rates were to be considered having adjusted for deprivation group, 15 300 fewer cancers would have been diagnosed in a period between 2006 and 2010. 9 The changing epidemiology of HNC, particularly in the Western world, 10,11 is a balance between a significant fall in the rates of tobacco and excess alcohol consumption, particularly in high-income countries, 12,13 and a rapid concurrent increase in the incidence of oropharyngeal squamous cell carcinoma. 9 The changing epidemiology of HNC, particularly in the Western world, 10,11 is a balance between a significant fall in the rates of tobacco and excess alcohol consumption, particularly in high-income countries, 12,13 and a rapid concurrent increase in the incidence of oropharyngeal squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…9 In a similar period (2007-2011), there was a yearly excess of 19 200 deaths. This rise of oropharyngeal cancer is associated with human papilloma virus (HPV) infection, 10 which is a biologically and phenotypically distinct type of HNC. This rise of oropharyngeal cancer is associated with human papilloma virus (HPV) infection, 10 which is a biologically and phenotypically distinct type of HNC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation